Transcatheter aortic valve implantation (TAVI) in cardiogenic shock: TAVI‐shock registry results. Issue 5 (6th July 2020) - Fraccaro, Chiara; Campante Teles, Rui; Tchétché, Didier; Saia, Francesco; Bedogni, Francesco; Montorfano, Matteo; Fiorina, Claudia; Meucci, Francesco; De Benedictis, Mauro; Leonzi, Ornella; Barbierato, Marco; Dumonteil, Nicolas; et al.
Abstract: Objectives: Aim of this study is to evaluate safety, feasibility, and mid‐term outcome of transcatheter aortic valve implantation (TAVI) in cardiogenic shock (CS). Background: Balloon aortic valvuloplasty in patients with severe aortic valve stenosis (SAS) complicated by CS is indicated but associated with a grim prognosis. TAVI might be a more reasonable treatment option in this setting but data are scant. Methods: From March 2008 to February 2019, 51 patients with severe aortic valvulopathy (native SAS or degenerated aortic bioprosthesis) and CS treated by TAVI in 11 European centers were included in this multicenter registry. Demographic, clinical, and procedural data were collected, as well as clinical and echocardiographic follow‐up. Results: The mean age of our study population was 75.8 ± 13, 49% were women, and mean Society of Thoracic Surgeons (STS) score was 19 ± 15%. Device success was achieved in 94.1%, with a 5% incidence of moderate/severe paravalvular leak. The 30‐day events were mortality 11.8%, stroke 2.0%, vascular complications 5.9%, and acute kidney injury 34%. Valve Academic Research Consortium‐2 early safety endpoint was reached in 35.3% of cases. At 1‐year of follow‐up, the mortality rate was 25.7% and the readmission for congestive heart failure was 8.6%. Conclusions: TAVI seems to be a therapeutic option for patients with CS and SAS or degenerated aortic bioprosthesis in terms of both safety and efficacy at early and long‐term follow‐up.